Efeitos de suplementos de “Whey Protein” e de albumina sobre os fatores de risco para litíase renal - Hattori, Camila Mithie [UNIFESP] (2016)
Objectives Protein supplements are consumed by athletes and recreationally active adults for an expected increase in muscle mass, improved exercise recovery and improved performance. We aimed to evaluate the effects of whey protein (WP) and albumin supplementation on the risk factors for nephrolithiasis in healthy subjects. Research Methods & Procedures WP or albumin supplements (one scoop/day) were administered for 3 days to eighteen healthy volunteers, with one week washout period between them. Serum and 24-hour urine samples were collected at baseline and after completing each phase of supplementation. All participants were asked to replicate their baseline diet during the subsequent urine collections. Results After WP or albumin, mean protein equivalent of nitrogen appearance (PNA) was significantly higher (p<0.001), but mean urinary calcium, phosphorus, sodium, potassium, uric acid, citrate, oxalate, magnesium, creatinine, pH and urinary saturation indices did not differ from baseline. Individual increases higher than 50% in urinary calcium were observed in 39% of the individuals and variable decreases in urinary pH in 44% and 67% of them, after WP or albumin, respectively. Increases higher than 50% in urinary sodium occurred in one third of them after albumin. Conclusion A short-term consumption of one scoop of WP or albumin by healthy subjects Anexos 63 under controlled diet did not induce significant changes in the mean values of lithogenic parameters. However, the wide individual variation observed for urinary calcium, sodium and pH suggest close monitoring of their levels and adequacy of diet in case of supplementation by stone formers.